Research on Determination of Polychlorinated Biphenyl, Organochlorine Pesticides and Polybrominated Biphenyl Ether in Wheat - ZHANG Wei; YANG Yong-tan; WANG Song-xue; LI Sen; LI Li; CAI Di (Liang you shipin ke-ji, 2022)
This study is objected to develop a gas chromatographic-tandem mass spectrometric method to determine the contamination level of polychlorinated biphenyls, organochlorine pesticides and polybrominated biphenyl ether in wheat. In this method, the hydrated wheat powder was extracted with ethyl acetate and purified with acidic silica (44%). The gas chromatography-tandem mass spectrometry which operated on a dynamic multiple reaction monitor (dMRM) acquisition mode was using for instrumental analysis. The quantitation was carried out with internal standard method. The results demonstrated that all target analytes have good quantitative linear range with excellent regression factor (R2>0.996), while highly brominated biphenyl ethers were with quadratic regression. The recovery of method was between 57.9% to 118.6% with relative standard deviations of 1.6%~10.7%. The method detection limits were between 0.001 ng/g and 1.108 ng/g as the highly brominated biphenyl ether gave relatively poor detection limits. This method is simple, rapid, accurate and low-cost, especially useful for the high-throughput analysis of trace persistent organic pollutants in wheat.